Women's Activities In Anticipation Of The Traps Of Illegal Online Loans In The District Area Of Medan City - Sembiring, Idha Aprilyana; Lubis, Tri Murti (Mahadi: Indonesia Journal of Law, 2025)
In the digital era, women are becoming more professional in using digital technology including digital financial services. In fact, not all online financial services have a good impact, such as illegal online loans that often harass women and lead to extortion, loan sharking and defamation. It occurs because of the ignorance of the public, especially women, regarding the risks of illegal online loans, both legally and economically. Persuasive effort is needed, through a community service activity held in Medan Kota District and inviting women who live there. Community service is using the Participatory Rural Appraisal method. It began with a pre-test to find out the extent of knowledge of 20 women and 10 government officials about illegal online loans. Lectures and discussions were heldto provide legal knowledge regarding legal and illegal online loans, a discussion of its benefits and legal protections. And ended with a post test to see changes in participants' thoughts about illegal online loans. The results of all tests are the participants gained understanding and enlightenment regarding online loans in general and how to provide legal protection for victims and perpetrators of illegal online loans, so that they can avoid being trapped in illegal online loans.